An Overview of Extreme Years in Quercus sp. Tree Ring Records from the Northern Moldavian Plateau - Nagavciuc, Viorica; Mursa, Andrei; Ionita, Monica; Sfeclă, Victor; Popa, Ionel; Roibu, Cătălin-Constantin (Forests, 2023)
In this study, we made use of a regional oak tree-ring network from six stands that cover the northern Moldavian Plateau (eastern Europe) to analyze how different tree ring parameters (i.e., early wood tree-ring width, late wood tree-ring width, and total tree-ring width) of Quercus sp. are influenced by the occurrence of extreme climatic events (e.g., long-lasting drought events). In order to explore the influence of extreme hydroclimatic events on tree ring width, we have selected each of the six most extreme positive and negative years of tree growth and addressed the seasonal cycle of tree growth in comparison with the main climatic parameters, then evaluated both the current and lagged consequences of extreme hydroclimatic events on tree ring width and the capacity of trees to recover. Our results indicate that the variability of oak tree ring width from the Moldavian Plateau is mainly influenced by the availability of water resources, and that an important limiting growth factor for Quercus sp. is the occurrence of long-lasting drought events, e.g., at least two years in a row with severe drought conditions.